2023
DOI: 10.1021/acsmaterialsau.3c00033
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Gold Nanoparticle Naproxen-Derived Conjugations in Ovarian Cancer

Abstract: Ovarian cancer, which is one of the most diagnosed cancer types among women, maintains its significance as a global health problem. Several drug candidates have been investigated for the potential treatment of ovarian cancer. Nonsteroidal anti-inflammatory drugs (NSAIDs) demonstrated anti-cancer activity through the inhibition of cyclooxygenase 2 (COX-2) and by inhibiting COX-2-dependent prostaglandin (PG) production. Naproxen is one of the most used NSAIDs and Naproxen-derived compounds (NDCs) may show potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Consistent with the findings from flow cytometry analysis (Figure b), we found that when B-CDs were combined with naproxen, a considerable cancer-killing efficacy was demonstrated through cytotoxicity evaluation. It appears that naproxen played a role in the cellular disruption of DNA conformation. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the findings from flow cytometry analysis (Figure b), we found that when B-CDs were combined with naproxen, a considerable cancer-killing efficacy was demonstrated through cytotoxicity evaluation. It appears that naproxen played a role in the cellular disruption of DNA conformation. , …”
Section: Discussionmentioning
confidence: 99%
“…In the face of the ongoing investigation into toxicity, the integration of nanoparticles into drug delivery systems remains achievable through active or passive targeting mechanisms. Drug loading processes encompass physical and chemical approaches, where physical encapsulation offers simplicity and cost-effectiveness but may suffer from off-targeted molecular degradation. , Conversely, chemical conjugation with polymer materials provides advantages such as hydrophobic drug solubility, controlled pharmacokinetics, and reduced drug release in large quantities. , A previous study evaluated tetrazine-functionalized boron-rich carbon dots, which demonstrated rapid clearance and low tumor absorption following intravenous administration in a mouse HER2-positive tumor model . Naproxen, a widely recognized nonsteroidal anti-inflammatory drug (NSAID), has recently garnered attention for its potential anticancer properties, as evidenced by its efficacy as a COX-2 inhibitor in clinical trials. Our previous study proved that a combination of naproxen with nanoparticles results in better activity regarding the treatment of several diseases. Despite these promising properties, there is limited research on the kinetic release model that typically occurs when B-CDs are combined with anticancer medications, both in vitro and in vivo. Consequently, it is crucial to evaluate the significance of drug release studies as a continuation of the efficacy of B-CDs therapy.…”
Section: Introductionmentioning
confidence: 99%